The Routledge companion to English studies - Leung, Constant 1950-; Street, Brian V. (London Routledge, 2014)
"The Routledge companion to English studies will re-define the discipline of English studies and provide an authoritative overview of this area. This handbook will take account of both historical trajectories and contemporary perspectives whilst also showcasing the state-of-the-art contributions made by the more established components of English language studies. It will also highlight new and under-explored dimensions of this field such as English as lingua franca and multimodality to provide cutting-edge account of this dynamic and diverse field. This collection of forty newly commissioned articles provides a comprehensive and up-to-date picture of the field of English language studies and will be an invaluable text for researchers in this area"--Provided by publisher.
Keywords: Englishlanguage -- History; Englishlanguage -- Study and teaching